United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes the current state of housing finance in the United States. Although a number of important steps have been taken to address the structural weaknesses exposed by the crisis in mortgage markets, comprehensive housing finance reform remains the largest piece of unfinished business. Mortgage markets, even eight years after the start of the crisis, continue to function with extensive government support. Reform of the government-sponsored enterprises, which remain in conservatorship, has stalled-generating uncertainty and complicating other policy initiatives. However, there has been progress in building other components for a well-functioning housing finance system.